Komunikasi Interpersonal Dalam Permainan Game Mobile Legends Untuk Menciptakan Kekompakan Tim WB Esports - Akmal Rizieq Fauzi; Iin Soraya; Sari Ekowati Hadi (Tamilis Synex: Multidimensional Collaboration, 2024)
The problem that will be discussed in this research is "How does interpersonal communication create cohesiveness in the WB Esports team", the aim of this research is "To find out interpersonal communication to create cohesiveness in the WB Esports team.". This research uses a qualitative research method where the research method is based on the philosophy of postpositivism, which is used to research the conditions of natural objects, with the research object being interpersonal communication in the Mobile Legends game to create cohesiveness in the WB Esports team. This research uses the Social Penetration Theory which is in line with interpersonal communication according to Irwin Altman & Dalmas Taylor "This self-disclosure is the main way a shallow relationship develops into a more intimate relationship. On the other hand, self-disclosure can easily lead to criticism of someone." The results of this study are based on 4 stages of social penetration theory, and 3 stages of interpersonal communication, each stage is associated with the results of interviews from 2 informants of the WB Esports team.